PENGABDIAN MASYARAKAT PENYULUHAN TENTANG RUMAH SEHAT KELURAHAN TANJUNG RHU PEKANBARU - Rahmi Pramulia Fitri; Tiara Puspita; Khesy Rahmavita; Nabila Riskia Wardani (STAI Darul Qalam Tangerang, 2022)
Definition of House (BP Guide) In general, the notion of a house is a building which is a place to live to get protection from all the natural conditions that surround it, such as rain, hot sun, and so on. A healthy house must have good air circulation, adequate lighting, clean water, proper disposal of waste water, and moisture-free floors and walls. The house must also meet psychological needs, namely comfort and good communication between family members. In the Bantargedang Kersanegara Tasikmalaya area, there are still houses that do not have proper toilets and waste management that is not well organized. so that with these conditions there will be risk factors that can cause various types of diseases. Through community service we conduct health education about healthy homes. It is hoped that this health counseling activity will provide benefits, namely providing increased knowledge and understanding to the community in the RT 04/RW 09 Bantargedang Kersanegara Cibeureum area, Tasikmalaya Regency, regarding healthy homes where people can feel comfortable and increase their productivity